319 Copy number variation of PRAME gene across dairy breeds. (7th December 2018) - Seleguim Chud, T; Bickhart, D; Cole, J; Baldi Rey, F; da Silva, M; Munari, D
Abstract: The PRAME gene plays an important role on reproduction function in cattle and that gene almost present in high copy number in the mammalian genome. Copy number variation (CNV) states have been used in population genetics studies to identify population divergences due to alterations in copy number regions or genes and to identify their impact on economic interest traits, including reproductive traits. The aim of this study was to identify the copy number differences of the PRAME gene within the Gir, Holstein, and Girolando breeds. We analyzed two whole genome sequencing datasets from Girolando bulls, 13 from Gir and five from Holstein. A read depth method was performed using the CNVnator software to detect the CNVs in each sample. To identify the population differentiation among the breeds, the Vst statistic was used. The Vst value (0.77) for the PRAME gene (BTA17:51252501-51660000) indicated a high level of population differentiation among the breeds. The average of the copy number on the PRAME region for the Gir bulls was 14.51 per animal, whereas Girolando and Holstein animals did not exhibit copy number variation in this specific region. Our findings suggested that the PRAME region is copy number variable only in the indicine lineage.This study identified positive selection on the PRAME gene in Gir cattle that may have originated from the domestication process.